Modeling hepatic steatosis with human adult stem cell-derived liver organoids - Liuyang Zhu; Sen Liu; Ze Wang; Yueyue Yang; Pinsheng Han; Wen Tong; Tianyu Zhao; Libo Wang; Tao Cui; Long Yang; Yamin Zhang (iScience)
Summary: Metabolic dysfunction-associated steatotic liver disease (MASLD) remains the most common chronic liver disease worldwide, and appropriate in vitro models are of great significance for investigating pathogenesis and drug screening of MASLD. In this study, human expandable cholangiocyte organoids were derived from adult stem cells of normal liver tissue. After differentiation, liver organoids (LOs) exhibited the functional characteristics and genomic features of mature hepatocytes. To induce steatosis, LOs were incubated with a gradient concentration oleic acid, and it was found that the model could recapitulate the development of lipid accumulation and inflammation. In addition, the drug sensitivity of the hepatic steatosis model was further verified through anti-steatosis drug testing. In summary, LOs have great potential for disease modeling, and the results indicate that the hepatic steatosis model may serve as a useful tool for exploring the molecular mechanisms and drug screening of MASLD.